Comparative behavioural observations demonstrate the ‘cleaner’ shrimp Periclimenes yucatanicus engages in true symbiotic cleaning interactions - Titus, Benjamin M. (R Soc Open Sci, 2017)
Cleaner shrimps are ecologically important members of coral reef communities, but for many species, cleaner status (i.e. dedicated, facultative and mimic), clientele and ecological role remain unverified or described. On Caribbean coral reefs, the spotted ‘cleaner’ shrimp Periclimenes yucatanicus forms symbioses with sea anemones that may serve as cleaning stations for reef fishes. The status of this species as a cleaner is ambiguous: only a single in situ cleaning interaction has been reported, and in the only test of its efficacy as a cleaner, it did not effectively reduce parasite loads from surgeonfish. It has subsequently been hypothesized by other authors to be a cleaner mimic. We conduct a comparative investigation of cleaning behaviour between P. yucatanicus and the ecologically similar, closely related, dedicated cleaner shrimp Ancylomenes pedersoni in Curacao, Netherlands Antilles. We provide the first detailed field observations on cleaning behaviour for P. yucatanicus and test multiple behavioural expectations surrounding mimicry in cleaning symbioses. We found that P. yucatanicus regularly signals its availability to clean, client fishes visit regularly and the shrimp does engage in true symbiotic cleaning interactions, but these are brief and our video reflects a species that appears hesitant to engage posing clients. In comparison to A. pedersoni, P. yucatanicus stations had significantly fewer total visits and cleans, and 50% of all cleaning interactions at P. yucatanicus stations were shorter than 10 s in total duration. Our behavioural observations confirm that P. yucatanicus is a true cleaner shrimp; we reject the hypothesis of mimicry. However, investigation is needed to confirm whether this species is a dedicated or facultative cleaner. We hypothesize that P. yucatanicus has a specialized ecological role as a cleaner species, compared to A. pedersoni.